Motivational strategies used by principals in the management of schools : the case of some selected secondary schools in the Fako Division of the Southwest Region of Cameroon - Acheck Timah, Apolline (2015)
ABSTRACT The study examined the Motivational Strategies of Principals in the Management of selected secondary Schools in Fako Division of the Southwest Region of Cameroon. The study was guided by three research objectives and three research questions. The descriptive survey design was used to collect data from a representative sample of the population using questionnaires for teachers and principals. The data was analyzed using means and standard deviation and presented on tables and histograms. The findings revealed that: motivational strategies of principals include those related to Empathetic, Supportive, caring and just on academic and disciplinary matters; positive leadership Characteristics/ Behaviors; and transformational leadership style. This is explained by the aggregate mean score of 3.293243 on a scale of 1 to 4. The findings revealed that motivation is significant in the teaching-learning process and is positively related to the teaching/learning process (3.572973). Finally, the economic state of the nation, the character of the school administrator, school physical environment, political image of the nation, school location and the financial status of the school; in that order are the factors that influence staff motivation in secondary schools. To conclude, the problem of the secondary schools is not teacher motivation by principals, but is due to other factors like; non-upgrade of teachers’ salaries by government since after the 1990s global economic meltdown. There is therefore a need for government to revisit the salary situation of teachers among other factors.